Bioelastomers Based on Cocoa Shell Waste with Antioxidant Ability. (21st June 2017) - Tran, Thi Nga; Heredia‐Guerrero, José Alejandro; Mai, Binh T.; Ceseracciu, Luca; Marini, Lara; Athanassiou, Athanassia; Bayer, Ilker S.
Abstract : In this study, a new strategy for the utilization of cocoa shell waste, a by‐product of cocoa industry, is presented for the development of new bioelastomers. The cocoa shell waste (CSW) is first micronized and then incorporated into single component acetoxy‐poly(dimethylsiloxane) (acetoxy‐PDMS) macromolecular matrix by a mixing process to produce bioelastomer composites with tunable properties. A detailed study is carried out to investigate the influence of micronized cocoa waste concentration on the curing process and on the properties of final materials. It is found that addition of CSWs has a strong effect on the curing behavior of PDMS due to establishment of an intermolecular hydrogen bond network between the two components. CSW bioelastomers are hydrophobic and exhibit good water barrier properties. In addition, the bioelastomers show effective antioxidant scavenging activity against 2, 2‐diphenyl‐1‐picrylhydrazyl free radical (DPPH) and 2, 2′‐azinobis(3‐ethylbenzothiazoline‐6‐sulfonic acid) radical cation (ABTS + ). The incorporation of micronized CSW into PDMS is also found to significantly enhance the Young's modulus of the elastomers. Hence, these antioxidant bioelastomers originating from food industry waste can be highly suitable as materials for active food packaging applications. Abstract : Direct utilization of micronized cocoa shell waste for the fabrication of antioxidant and hydrophobic bioelastomers containing significant portion of cocoa shell waste is demonstrated by a simple, energy‐saving mechanical blending process without any chemical treatment or extraction steps.